Implementasi Algoritma SHA-3 Dan ElGamal Untuk Otentikasi Piagam Penghargaan Berbasis Digital Signature - Annisa Apriliani; Nelly Astuti Hasibuan; Dito Putro Utomo (SNASTIKOM, 2022)
The rapid development of technology today is very possible for the occurrence of various forgeries and frauds that are carried out to take profits unilaterally. One of them is the falsification of a certificate of appreciation that canbe easily carried out by irresponsible parties. An award certificate is an important file that proves theachievements of a person in a particular activity or competition. This is what gives rise to a lot of people who tryto forge certificates of appreciation for their personal interests, both work and education. Therefore, a system isneeded to test the authenticity of the award charter. With a series of testing steps carried out, it can be concludedwhether the award certificate is authentic or not. To avoid falsification of document files, it is necessary to applya digital signature with a cryptographic method. Digital signatures or better known as digital signatures can helptest the authentication of a document, especially a certificate of appreciation. When the digital signature has beenapplied to the award certificate, the award recipient can check whether the file is authentic or has been modified.The application of digital signatures goes through 2 stages, namely the signing and verification process. Signingis the stage of forming a digital signature by combining the SHA-3 and ElGamal algorithms. The authenticity ofthe file can be seen by carrying out the verification process, which is the process of comparing the hash value ofthe received file with the actual file hash value. This research produces an analyzation about process ofauthentication using digital signature.